Perilaku Kekuatan Beton dengan Partikel Gelas dan Karet Ban Bekas Sebagai Pengganti Pasir Alam - Yansiku, Sandy Immanuel (Departemen Teknik Sipil dan Lingkungan IPB, 2018)
This paper presents the results of experimental investigation into the behaviour of concrete mixed with recycled-based materials as partial replacement of natural sand. Various properties: compressive, split tensile and flexural strength were investigated through either single or combination replacement categories in which glass sand, rubber sand, and recycled concrete aggregate were specifically proportioned. Test results indicate that certain replacement types of possibly achieve sufficient strength and physical behaviour to replace normal concrete. Single replacements typically generate higher compressive, tensile and flexural strength than combination types. Concrete with lower content of alternative material exhibited comparable strength relative to the original concrete. The workability of higher angular surface material such as glass sand and rubber sand generated higher workability. Keywords: concrete strength; glass; rubber; particles; replacement